Tanggungjawab Sekretaris Desa Papringan Dalam Kasus Sengketa Tanah di Desa Papringan - Suwarto, Suwarto; Santoso, Aris Priyo Agus; Habib, Muhamad; Elisanti, Evi (Fakultas Syariah INSURI Ponorogo, 2023)
The aim of this research is to determine the responsibilities and obstacles of the Papringan village secretary in cases of land disputes in Papringan Village. The research location is at the Papringan Village Office, Kaliwungu District, Semarang Regency. The research method used an empirical juridical legal science approach. Primary data was obtained through interviews, discussions with village secretaries, parties in land disputes, village communities to provide information regarding the resolution of land dispute cases through mediation. Secondary data was obtained from library literature. Data collection techniques used were literature studies, interviews and documentation. The qualitative descriptive data analysis technique used an interactive analysis model. The results of the research show that the responsibility carried out optimally by the village secretary can improve services, development and empowerment of the village both individually and in the village community, so that the implementation of the duties and functions of the village secretary in resolving land dispute cases is more focused in a planned, orderly manner in order to achieve the expected goals. The Village Secretary's responsibilities are carried out efficiently, effectively and are able to reduce the emergence of problems in resolving land dispute cases through mediation. The obstacles of the Papringan village secretary in the land dispute case in Papringan Village are internal and external factors. The conclusion of this research is that the responsibility of the village secretary in resolving land dispute cases in Papringan Village is good enough and optimal so that obstacles to resolving land dispute cases can be minimized.